Roles and Functions of Kawedanan Radya Kartiyasa in Managing Kraton Yogyakarta Museum - Yohana Raras Pritandari; Yohana Ari Ratnaningtyas; Trisna Pradita Putra (TUMATA: Journal of Arts and Cultural Management, 2024)
Kraton Yogyakarta Museum is a non-profit institution owned by Kraton Yogyakarta, which has four units: Kedhaton, Wahanarata, Pagelaran, and Tamansari. In 2023, Kraton Yogyakarta Museum was started to be managed by Kawedanan Radya Kartiyasa in terms of museum assets and tourism. This research described roles and functions of museum management theory by Lord and Lord (2009) compared with Kawedanan Radya Kartiyasa management practice. This research used descriptive qualitative research method, and data collection technique carried out by observations, interviews and literature review. Results found that the role of Kawedanan Radya Kartiyasa is to manage museum administrations and managements. The head or Penghageng of Kawedanan Radya Kartiyasa is a level two Penghageng, so every mandate, coordinations, and approvals are given by GKR Bendara as Penghageng KHP Nitya Budaya. Five roles of museum management, to inspire, to communicate, to lead, to control, to evaluate were done by the coordinators. Kawedanan Radya Kartiyasa applied the functions of museum management, administrations, collection assets, and museum activities managed by two different Kawedanan. Four functions, administration, research, display, interpretation, were managed by Kawedanan Radya Kartiyasa. Two functions, documentations and preservation in conservation and curator were managed by Kawedanan Purayakara. One function collecting was done by Penghageng KHP Nitya Budaya approval. Kawedanan Radya Kartiyasa and Kawedanan Purayakara are Kawedanan under KHP Nitya Budaya supervision.